Antecedents of the Cuban Agricultural Policies of the 1990s - José Alvarez (EDIS)
The three primary forces leading to the implementation of new economic policies for Cuban agriculture during the 1990s are the subject of this fact sheet. These policies were not the result of abrupt and irrational decisions by the Cuban leadership. They originated in three unrelated events that unfolded separately and almost simultaneously: (1) the relationship between state intervention and poor agricultural performance that was aggravated during the 1980s, (2) the demise of socialism in the countries of Eastern Europe and the Soviet Union, and (3) the reinforcement of U.S. economic sanctions against Cuba. This is EDIS document FE485, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.